Green metric-based RP-HPLC method development and validation with force degradation study of neratinib using QbD approach - Sanjay Sawant; Jyoti Tangde (Discover Chemistry)
Abstract The present research study focuses on the development and validation of the reverse phase-high performance liquid chromatography (RP-HPLC) technique for the estimation of neratinib with a forced degradation study based on the quality by design (QbD) approach. A three-level, two-factorial design has been used for method optimization, while a two-factorial, two-level design was used for the force degradation study using design expert software. The chromatographic separation was performed using a C18 column at a 217 nm wavelength with a 1.00 mL min–1 flow rate. Risk assessment and statistical analysis were performed to demonstrate the significance of design. The greenness of the method was confirmed using the AGREE tool. The validation was carried out using International Council for Harmonization (ICH) Q2R2 guidelines and results found with linearity, R2 = 0.999. Retention Time was observed at 4.266 min. The Detection Limit (DL) and Quantitation Limit (QL) were found to be 0.4480 µg/mL and 1.3575 µg/mL respectively. We found the relative standard deviation (%RSD) for intraday precision to be 1.3423 and for interday precision to be 1.483. The recovery was achieved 99.94-100.26%. The forced degradation studies showed that neratinib does not degrade in alkaline conditions but is sensitive to acidic, thermal, photolytic, and oxidative stress environments. The resulting method with QbD and a green approach holds potential application in routine analysis of neratinib in bulk and pharmaceutical formulations in compliance with Q2 R2 ICH guidelines.